FRI E'DAH - Bitilis, Farah Farhanah; Mudin, Idirah; Tugimin, Farhanna Edna; Ajamain, Lailan Azidah; Jaya, Rosijah (2015)
FRI E'DAH is a company that produce a product which is chair. Our company located in Jalan Kuhara 91007, Tawau, Sabah that allows the society to have their chair needs satisfied in one convenient location. FRI E'DAH company serves men, women, children and accepts appointments as well as walk-ins. FRI E'DAH also sell the product that have many function that can satisfied their needs and able to serve the entire family in one quick, convenient visit. While there are many product of chair like FRI E'DAH. FRI E'DAH will excel due to its attention to detail regarding customer want. Through customer attention, FRI E'DAH will slowly but surely gain market share as it product for the society, creating long-term relationship. Lastly, FRI E'DAH location will allow attract unemployment to join our company and give job opportunity to them based on requirement that needed from our company. Then, they will spread our company and attract more people. People across Malaysia have decided to use our product when they want to fulfill their need, for example they want to use chair for different purposes. But at the same time, they need to use chair for sit. So, we make an innovative to make a chair in a multi-function that we can called as '2 in 1'. It is means that, our chairs can use for sit and also can use as ladder that combine in one product only. We, FRI E'DAH saw the opportunity that this business has the potential of success provided that it is handled efficiently and excellent. The people have always needed something new and different in this world. Thus, make them satisfies and meet their needs and expectations. FRI E'DAH make an innovative chair. FRI E'DAH sees this way as a way to prosper in this markat by taking advantage of all these people's need.